ANALISIS PENGELOLAAN DESA WISATA SEBAGAI PARIWISATA ALTERNATIF DI BALI - I Wayan Pantiyasa; I Nyoman Urbanus (Institut Pariwisata dan Bisnis Internasional, 2016)
The â€œMass-Tourismâ€ that has been developed in Bali, eventually has marginalized the local people. It has obviously also caused a lot of problems including the changing of land use, urbanization, the increase of criminals, narcotic abuse, degradation of local values of life, etc. The development of â€œDesa Wisataâ€ (community Based Tourism) is the answer of those mentioned above problems. This research aims to analyze the management of â€œDesa Wisataâ€(community Based Tourism), Tourist perception of service provided for clients, and the observation of the local values. The method of his research is survey, observations, interviews, documentations, and questionnaire. The results shows from management perspectives that the â€œDesa Wisataâ€ (community Based Tourism)Â has not been professionally managed in term of administrations including reservation system, reception of tourist, accounting, and data base.All those weaknesses were caused by the lack of competence of the human resources. the â€œDesa Wisataâ€ (community Based Tourism) has not yet decided the planning of the development of the village. The operational just operate without well organized plan. There is no master plan for a strategic development, no innovations and no promotion planning. The Tourist perception ofÂ services provided are Excellent-given to the safety in the room, hospitality of the staff, menu variations, food and beverage presentation, tourist attraction and empathy of the management., Good-given to the reception during he arrival and luggage-handling, comfortness of accommodation, room amenities availability, and the food taste , Fair-given to the cleanliness of rooms and toilets, cleanliness of cutleries and restaurants and garbage handling, Poor-givenÂ to the cleanliness of the environment including receptions, roomÂ availability , food and beverage provided scored as above average. Sanitation and hygiene need to be upgraded and the waste management is still very low. It is recommended for the management to provide training programs especially in increasing the staffsâ€™ foreign language capability mostly English and French.Â